Wet chemical synthesis of metal oxide nanoparticles: a review - Nikam, A. V; Prasad, B. L. V; Kulkarni, A. A (CrystEngComm, 2018)
Metal oxide nanoparticles are an important class of nanomaterials that have found several applications in science and technology. Through wet chemical synthesis, it is possible to achieve selective surface structures, phases, shapes, and sizes of metal oxide nanoparticles, leading to a set of desired properties. Wet chemical synthesis routes allow fine tuning of the reaction conditions (temperature, concentration of substrate, additives or surfactants, pH, etc. ) to afford the desired nanomaterials. In this review article, we highlight recent developments in the wet chemical synthesis of metal oxide nanoparticles to provide great control over the quality of the obtained nanomaterials. The review critically evaluates the different wet chemical methods for scalable production of metal oxide nanoparticles to satisfy the growing industrial demand for nanomaterials. Special attention is paid to continuous flow synthesis of metal oxide nanoparticles. Metal oxide nanoparticles are an important class of nanomaterials that have found several applications in science and technology.